Microplastics pollution in sediment of Serang River Kulon Yogyakarta Province - Ismiyati; Utami, Inggita; Tricahya, Fahmi Hermawan; Pidianto; Rahmawati, Suci; Ramadhanti, Annesa Mahsa; Sakti, Anjar Dimara (Jurnal Rekayasa Proses, 2023)
Microplastics that can harm living things have been found in large rivers in Yogyakarta Province to the digestive tract of fish. However, rivers in the suburban areas of the province, such as the Serang River, have not yet been identified, although many local communities still use them. This study aimed to analyze the abundance, type of polymer, and characteristics of microplastics found in Serang River sediments. Sampling was carried out in December 2019 in the upstream, midstream, and downstream areas of the river. Six sediment samples were taken from each area and randomly divided into two stations. Each sediment sample was then dried, weighed dry, separated the microplastics, observed visually, calculated the abundance of microplastics, grouped shape, size, and color (characteristics), identified the type of polymer by Fourier-transform infrared spectroscopy (FTIR) test, and analyzed quantitatively descriptively and inferentially. The results showed that microplastics were present in all samples with an abundance range of 148.88 to 384.58 particles kg-1. The abundance of microplastics in Serang River sediments was highest in the downstream area, with an average of 321.99 ± 46.76 particles kg-1. The microplastic was identified as a polyethylene polymer as the main ingredient for making single-use plastics. The characteristics of microplastics in Serang River sediments are dominated by a size range of 10-50 m, in the form of fragments and films, and transparent colors.